Transforming Health Care Through Information - Lorenzi, Nancy M.; Ash, Joan S.; Einbinder, Jonathan; McPhee, Wendy; Einbinder, Laura (Health Informatics,, 2005)
Based on case studies, this book illustrates the complex challenges faced by healthcare administrators when implementing changes in technology.